A nano flow cytometer for single lipid vesicle analysis. Issue 5 (27th January 2017) - Friedrich, Remo; Block, Stephan; Alizadehheidari, Mohammadreza; Heider, Susanne; Fritzsche, Joachim; Esbjörner, Elin K.; Westerlund, Fredrik; Bally, Marta
Abstract : A nano flow cytometer to quantify lipid vesicles and to analyse fluorescence intensity on a single vesicle level is presented. Abstract : We present a nanofluidic device for fluorescence-based detection and characterization of small lipid vesicles on a single particle basis. The device works like a nano flow cytometer where individual vesicles are visualized by fluorescence microscopy while passing through parallel nanochannels in a pressure-driven flow. An experiment requires less than 20 μl sample volume to quantify both the vesicle content and the fluorescence signals emitted by individual vesicles. We show that the device can be used to accurately count the number of fluorescent synthetic lipid vesicles down to a vesicle concentration of 170 fM. We also show that the size-distribution of the vesicles can be resolved from their fluorescence intensity distribution after calibration. We demonstrate the applicability of the assay in two different examples. In the first, we use the nanofluidic device to determine the particle concentration in a sample containing cell-derived extracellular vesicles labelled with a lipophilic dye. In the second, we demonstrate that dual-color detection can be used to probe peptide binding to synthetic lipid vesicles; we identify a positive membrane-curvature sensing behavior of an arginine enriched version of the Antennapedia homeodomain peptide penetratin. Altogether, these results illustrate the potential of this nanofluidic-based methodology for characterization and quantification of small biological vesicles and their interactors without ensemble averaging. The device is therefore likely to find use as a quantitative analytical tool in a variety of fields ranging from diagnostics to fundamental biology research. Moreover, our results have potential to facilitate further development of automated lab-on-a-chip devices for vesicle analysis.